La dinámica de los préstamos de consumo en 2020 en Argentina: Una aproximación mediante modelos de corrección de error - Maximiliano Gómez Aguirre; Ariel Krysa (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2022)
– With the aim of quantifying the effect of the decrease in interest rates on consumer loans (both credit cards and personal loans, in local currency to the non-financial private sector) in Argentina between March and December 2020, monthly error correction models are estimated, and counterfactual scenarios are developed for each of the credit lines. The sample that is used includes the period 2004-2020 and the determinants are the corresponding interest rates and economic activity measures. As an alternative case, it is assumed that interest rates would have been fixed in 2020 at the values of February that year and/or that the parameters of elasticities that operated in the consumer credit markets were those associated with the pre-COVID-19 context. The counterfactual scenarios implemented within the econometric models suggest that the decline in the interest rate would have cushioned, with different magnitudes throughout 2020, the fall caused by effects of the pandemic both in the credit cards and personal loans real balances.
Keywords: C01; E21; E50; 330; consumption credit; COVID-19 crisis; Argentina; credit cards; personal loans; Verbraucherkredit; Revolvierender Kredit; Kreditzins; Coronavirus; Argentinien